Ідеологічні аспекти протидії (профілактики, превенції) та боротьби зі злочинністю крізь призму духовно-ціннісної складової: регіоналістський та загальнодержавний акцент - Кріцак, І. В.; Kritsak, I. V.; Іван Кріцак (Юридичний науковий електронний журнал. - 2022. - № 5. - С. 41-45, 2022)
Досліджено актуальні питання ідеологічних мотивів та основ кримінологічної і кримінально-правової протидії (профілактики, превенції) злочинності в аспекті подальшого розроблення та популяризації духовно-ціннісної концепції праворозуміння. Наголошується на особливій ролі такого попередження з соціально-духовних позицій та повсякденного досвіду в аспекті «фізичного та духовного здоров’я нації», «сучасних хвороб суспільства» у напрямку вироблення альтернативних засобів протидії. В такий спосіб актуалізується роль сучасної кримінології і, як результат, здобуття нею міждисциплінарного статусу з необхідністю її подальшого розроблення у руслі кримінотеології. Особлива роль у цих процесах покладається на заклади вищої освіти поліцейського профілю, поширення науки у всіх правоохоронних структурах.

The article raises topical issues of ideological motives and bases of criminological and criminal-legal counteraction (prophylaxis, prevention) of crime in the aspect of further development and popularization of spiritual-value concept of legal understanding. Emphasis is placed on the special role of such prevention from a socio-spiritual standpoint and daily experience in terms of «physical and spiritual health of the nation», «modern diseases of society» in the direction of developing alternative means of counteraction. In this way, the role of modern criminology is actualized and, as a result, its acquisition of interdisciplinary status with the need for its further development in the field of criminology. A special role in these processes is entrusted to higher education institutions of police profile, dissemination of science in all law enforcement agencies. In this aspect, the emphasis is on «point» prevention and fight against crime at the regional level, the need of ideological propaganda of crime prevention in accordance with the famous "broken window theory" and further emphasis on alternative punishments as opposed to violent crime policies. Continuous monitoring of various aspects of public life and scientific achievements can greatly contribute (the creation of "criminological monitoring groups" so-called «criminological political technologists») in the direction of convergence of theory and practice. Transformation of criminology from social and legal science and academic discipline and its acquisition of interdisciplinary status due to through the usage of a wide range of research methods (critical approach to social reality, scientific assessment of the situation, bold innovative ideas) strengthens its optimizing function with the prospect of creating research and innovation centers in practical divisions of law enforcement agencies (it is about the convergence of theory and practice through the collection, accumulation, processing and analysis of information, the general positive and negative manifestations of society), which will contribute to the development of advanced methods of prevention and combating crime. Priority of moral and spiritual values in terms of developing criminological and criminal law (preventive) policies and ideology of the state on the principle of «general requirements for all and individual approach to each» sets the rhythm in achieving the goals of the criminal justice system, effective cooperation between the church and law enforcement agencies, constant monitoring of crime and scientific achievements in various fields, which forms a qualitatively new system and ideological paradigm of the policy of appropriate counteraction and struggle.

Исследованы актуальные вопросы идеологических мотивов и основ криминологического и уголовно-правового противодействия (профилактики, превенции) преступности в аспекте дальнейшей разработки и популяризации духовно-ценностной концепции правопонимания. Отмечается особую роль такого предупреждения с социально-духовных позиций и повседневного опыта в аспекте «физического и духовного здоровья нации», «современных болезней общества» в направлении выработки альтернативных средств противодействия. Таким образом актуализируется роль современной криминологии и, как результат, получение ею междисциплинарного статуса с необходимостью дальнейшей разработки в русле криминотеологии. Особая роль в этих процессах возлагается на учреждения высшего образования полицейского профиля, распространение науки во всех правоохранительных структурах.
Ideological aspects of counteracting (preventing) and combating criminality through the prism of spiritually-valued component: regionalistic and statewide accent
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; протидія злочинності; crime prevention; противодействие преступности; кримінотеологія; criminology; криминотеология; духовно-ціннісна складова; spiritual and valuable component; духовно-ценностная составляющая; функції кримінології; functions of criminology; функции криминологии; кримінально-правова політика; criminal law policy; уголовно-правовая политика